Testing the environmental Kuznets curve hypothesis in terms of ecological footprint and CO2 emissions through energy diversification for Turkey - Acaroglu, Hakan; Kartal, Hatice Melissa; Marquez, Fausto Pedro Garcia (SPRINGER HEIDELBERG, 2023)
This research work analyzes the relationship between environmental degradation, economic growth, trade openness, primary energy consumption, coal consumption, and hydroelectricity consumption in Turkey from 1971 to 2015 using the autoregressive distributed lag (ARDL) time series approach through the hypothesis of the environmental Kuznets curve (EKC). Carbon dioxide (CO2) emissions and ecological footprint are both used as indicators of environmental degradation, which employs six different models. According to the results found in this study, while trade openness increases CO2 emissions, it decreases ecological footprint in the long-run. Coal consumption raises both CO2 emissions and ecological footprint. While hydroelectric energy reduces CO2 emissions, it has no effect on the environment. The results demonstrate that the EKC hypothesis is correct for both CO2 emissions and Turkey's ecological footprint. The threshold points are investigated as $18,704, $16,361, and $13,571 in models, where CO2 emissions are the dependent variable. In models where the ecological footprint is the dependent variable, the investigated threshold points of $11,824, $11,821, and $15,476 are higher than the gross domestic product (GDP) per capita during the analysis periods. Furthermore, the findings highlight the importance of renewable energy use in reducing environmental degradation and coal use in increasing environmental degradation. These findings can shed light on the importance of transition to renewable energy sources (i.e., hydroelectricity consumption), from fossil fuels (i.e., coal consumption), related to future planning in energy diversification for Turkey.
Keywords: The EKC hypothesis; Ecological footprint; CO2 emissions; Economic growth; Renewable energy consumption; Energy diversification; ARDL bounds test; FOREIGN DIRECT-INVESTMENT; RENEWABLE ENERGY; ECONOMIC-GROWTH; NONRENEWABLE ENERGY; CONSUMPTION; INCOME; TRADE; URBANIZATION; DEGRADATION; POLLUTION; Environmental Sciences & Ecology